Role of Youth Organizations in Anticipating Money Politics and Racial Issues for The Success of the 2024 Election (Study the Karya Muda Youth Organization, Kedungjambal Village, Tawangsari District, Sukoharjo Regency) - Widiatmaka, Pipit; Sugiyanto, Arissander; Ramdhani, Alifah; Mahendra, Muhammd Guruh (JURNAL LITBANG PROVINSI JAWA TENGAH, 2023)
The holding of elections in Indonesia in 2019 is indicated to be tainted by money politics. Many actors can play a role in preventing money politics, including the Election Supervisory Board (Bawaslu), the Honorary Board of Election Organizers (DKPP), formal and non-formal educational institutions, as well as non-governmental organizations (NGOs), including Karang Taruna. This study aims to determine the role and constraints of Karya Muda cadets in preventing money politics and SARA issues in the 2024 election. This research uses a qualitative approach with a descriptive method, and the location of the research is Karang Taruna Karya Muda in Kedungjambal Village, Tawangsari District, Sukoharjo Regency. Data collection techniques include in-depth interviews, observations, and document studies. The data analysis technique used is interactive data analysis. The results showed Karya Muda's role in anticipating money politics and SARA issues to succeed in the 2024 elections through several activities, namely holding regular meetings with community leaders, Halal Bi Halal activities, 3) socialization with the neighbourhood community, commemorating Indonesian Independence Day, recitation, and sports. The obstacles experienced by Karya Muda are that there are still people doing money politics, there is intervention from village officials to choose one of the leadership candidates, and there are still some Karya Muda members who are influenced by money politics.